Sediment routing and basin evolution in Proterozoic to Mesozoic east Gondwana: A case study from southern Australia - Barham, Milo; Reynolds, S.; Kirkland, Chris; O'Leary, Mick; Evans, Noreen; Allen, H.; Haines, P.; Hocking, R.; McDonald, B. (Elsevier BV, 2018)
Sedimentary rocks along the southern margin of Australia host an important record of the break-up history of east Gondwana, as well as fragments of a deeper geological history, which collectively help inform the geological evolution of a vast and largely underexplored region. New drilling through Cenozoic cover has allowed examination of the Cretaceous rift-related Madura Shelf sequence (Bight Basin), and identification of two new stratigraphic units beneath the shelf; the possibly Proterozoic Shanes Dam Conglomerate and the interpreted Palaeozoic southern Officer Basin unit, the Decoration Sandstone. Recognition of these new units indicates an earlier basinal history than previously known. Lithostratigraphy of the new drillcore has been integrated with that published from onshore and offshore cores to present isopach maps of sedimentary cover on the Madura Shelf. New palynological data demonstrate progression from more localised freshwater-brackish fluvio-lacustrine clastics in the early Cretaceous (Foraminisporis wonthaggiensis – Valanginian to Barremian) to widespread topography-blanketing, fully marine, glauconitic mudrocks in the mid Cretaceous (Endoceratium ludbrookiae – Albian). Geochronology and Hf-isotope geochemistry show detrital zircon populations from the Madura Shelf are comparable to those from the southern Officer Basin, as well as Cenozoic shoreline and palaeovalley sediments in the region. The detrital zircon population from the Shanes Dam Conglomerate is defined by a unimodal ~1400 Ma peak, which correlates with directly underlying crystalline basement of the Madura Province. Peak ages of ~1150 Ma and ~1650 Ma dominate the age spectra of all other samples, indicating a stable sediment reservoir through much of the Phanerozoic, with sediments largely sourced from the Albany-Fraser Orogen and Musgrave Province (directly and via multiple recycling events). The Madura Shelf detrital zircon population differs from published data for the Upper CretaceousCeduna Delta to the east, indicating significant differences in sediment provenance and routing between the Ceduna Sub-basin and central Bight Basin.